Just small talk? The impact of interpersonal interaction in virtual web communities on new-product adoption. (1st January 2013) - Botzenhardt, Achim; Heinrich, Daniel; Campbell, Colin
While marketers have largely recognised website design and its value, interaction mechanisms are widely underexplored features of virtual communities. We argue that not only the presence of interpersonal interaction – but also its type – play key roles in how consumers experience virtual communities. In our study, we demonstrate a main effect of interpersonal interaction on relevant variables of consumers' willingness to adopt a new product introduced in the virtual community. Moreover, we analyse the role different actors can play. Our findings reveal the importance of company-representing experts in such virtual environments, shedding light on a new tool for marketers to further benefit from web communities.